EU Energy Security - Multidimensional Analysis of 2005-2014 Development - Obadi, Saleh Mothana; Korcek, Matej (International Journal of Energy Economics and Policy, 2017)
Concept of energy security has been subject to multiple attempts for its conceptualization. Nowadays generally accepted approach is based on multiple dimensions and incorporates factors of energy availability, energy affordability, energy efficiency and environmental stewardship. This paper used z-scored standardization methodology in order to empirically examine the development of overall energy security via synthesizing the contributions of individual dimensions. We took into account eleven distinct variables which describes the each dimension. We found out, that most important common denominator that distinguishes the most secured countries from its peers within EU is their ability to generate energy indigenously due to its natural endowments. Our analysis further revealed that dimensions that are covered under common energy policies (energy efficiency and environmental stewardship) show signs growing cohesion across countries. However countries which improved their overall energy security relied primarily on their affordability dimension. We need to add that each dimension contributed its significant share to the total energy security index development. Keywords: Energy Security, European Union, Energy Security Index, Z-score Standardization JEL Classifications: Q2, Q3, Q4